Formation of Professional-Pedagogical Image of Teachers of Higher Educational Establishments - Vashak, Oksana; Martirosyan, Ludmila (Pedagogical Discourse, 2019)
The article deals with the problems of forming the image as the main component of professionalism at a higher educational institution, revealing the peculiarities of «personality image», «pedagogical image», «professional image» notions; the role of pedagogical imageology in a specialist professional formation has been determined; the main structural components of the teacher’s professional- pedagogical image formation have been offered; emphasis is placed on the importance of the specificity of the image as an integral part of pedagogical activity professionalism; questions have been raised about creating a positive image of higher education modern institutions. The purpose of the paper is to provide scientific substantiation of the importance of forming professional-pedagogical image of higher educational institution teachers. The article covers the problem of the image of the teacher as the integrative quality of personality, synthesis of intellectual, linguistic, environmental and artistic culture. The article reveales the factors of personality forming-habilitary, image of environment, verbal image. It emphasizes the importance of studying the problem of specificity of the image of institution of higher education as an integral part of professionalism in its pedagogical activities. Emphasizes the importance of self-development and self-improvement to higher school teachers to increase the level of professional competence. Revealed importance of development creativity in the process of making pedagogical image. The importance of owning a high level of pedagogical skills of specialists is emphasized, as demonstrated by the highest form of activity of a teacher, based on humanities and disclosed in the appropriate use of methods and means, the role of specialists as the main subjects of creating a positive image of higher education institutions is shown. The article presents some scientific achievements in imagology, where previously documented important problems and issues of professional image of the educator, improving the professionalism of the future specialists of the educational industry, forming the basics of positive pedagogical image, as well as psychological peculiarities of teacher’s competence in shaping own image.